2019
DOI: 10.3390/ijerph16132361
|View full text |Cite
|
Sign up to set email alerts
|

Walking and Sun Protective Behaviors: Cross-Sectional Associations of Beneficial Health Factors

Abstract: Sun protective behaviors and physical activity have the potential to reduce cancer risk. Walking is the most common type of physical activity in the United States, but it is unclear whether sun protective behaviors differ by categories of walking, such as leisure versus transportation walking. We examined whether sun protective behaviors varied by category or duration of walking in the 2015 National Health Interview Survey (N = 26,632), age ≥ 18 years. We used logistic regression to estimate sunscreen use, sun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…A recent Australian study showed widespread and increased use of sunscreen among adults, and physical activity was associated with lower shade-seeking behavior but was associated with higher odds of other sun protection behaviors, such as sun protective clothing and accessories [24,25]. In another study of Australian adults, those who met the physical activity guidelines were more likely to apply sunscreen while outdoors, whereas those who did not meet the guidelines were more likely to seek shade [26,27]. Shade-seeking behavior is influenced by a variety of factors other than sunscreen use, and further research may investigate whether longer periods of physical activity explain higher health perceptions and sun-protective behaviors.…”
Section: Discussionmentioning
confidence: 98%
“…A recent Australian study showed widespread and increased use of sunscreen among adults, and physical activity was associated with lower shade-seeking behavior but was associated with higher odds of other sun protection behaviors, such as sun protective clothing and accessories [24,25]. In another study of Australian adults, those who met the physical activity guidelines were more likely to apply sunscreen while outdoors, whereas those who did not meet the guidelines were more likely to seek shade [26,27]. Shade-seeking behavior is influenced by a variety of factors other than sunscreen use, and further research may investigate whether longer periods of physical activity explain higher health perceptions and sun-protective behaviors.…”
Section: Discussionmentioning
confidence: 98%
“…The few studies available to date have identified deficits in sun protection. Duquia et al 18 and Tribby et al 19 showed that only about one‐third of their population‐based samples used sunscreen during sports activity outdoors. The use of sun protection measures other than sunscreen has been little studied to date.…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies have measured time spent outdoors, physical activity and sunburn risk concurrently. Walking, the most common physical activity in the U.S., was not generally associated with sunburns [ 15 ]. One sun protective behavior, using sunscreen, is associated with increased odds of sunburns [ 13 ], whereas other sun protective behaviors, such as seeking shade, wearing a hat, and sun protective clothing, are associated with decreased risk of sunburns [ 16 ].…”
Section: Introductionmentioning
confidence: 99%